2014
DOI: 10.2147/clep.s62392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical performance and cognitive performance measures among community-dwelling older adults

Abstract: PurposeCognitive impairment is correlated with physical function. However, the results in the literature are inconsistent with cognitive and physical performance measures. Thus, the aim of this study was to determine the association between cognitive performance and physical function among older adults.MethodsA total of 164 older adults aged ≥60 years and residing in low-cost housing areas in Kuala Lumpur, Malaysia participated in this study. Cognitive performance was measured using the Mini Mental State Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
3
12
0
2
Order By: Relevance
“…In our previous study, agility was demonstrated to be related to cognitive function. 42 Agility significantly improved with balance exercises 43 in older adults. Agility may not have appeared as a predictor for physiological falls risk in this study, probably because balance and age have accounted for this effect.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, agility was demonstrated to be related to cognitive function. 42 Agility significantly improved with balance exercises 43 in older adults. Agility may not have appeared as a predictor for physiological falls risk in this study, probably because balance and age have accounted for this effect.…”
Section: Discussionmentioning
confidence: 95%
“…In several previous studies, the significance of optimum biophysical health, lifestyle and dietary habits, as well as some psychosocial domains with cognitive function and successful aging, have been emphasized. 15,[17][18][19] The Singapore Longitudinal Aging Study (SLAS) is the most comparable multiethnic population-based cohort study with the present study. 8 In SLAS, the authors aimed at investigating psychosocial, lifestyle, behavioral, biomedical and healthcare determinants of aging and age-related health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, alterações na função cognitiva parecem ter relação com o desempenho físico do idoso (Won et al, 2014). Um estudo nos Estados Unidos observou que idosos com declínio em funções como atenção e velocidade de processamento também apresentaram prejuízos no desempenho de habilidades como força de preensão e marcha (McGoughet al, 2013).…”
Section: Discussionunclassified
“…O próprio processo de envelhecimento favorece a redução da reserva fisiológica em diferentes sistemas, acarretando diminuição da capacidade de gerar respostas adaptativas frente a estímulos externos. Nesse sentido, contribui para perda progressiva do desempenho físico e alterações do estado cognitivo do idoso, expondo-o, assim, a maior vulnerabilidade (Won et al, 2014;Blankevoor et al, 2013).…”
Section: Introductionunclassified